2017
DOI: 10.1002/jmri.25606
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of malignancy by a radiomic signature from contrast agent‐free diffusion MRI in suspicious breast lesions found on screening mammography.

Abstract: 1 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:604-616.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 38 publications
5
83
1
7
Order By: Relevance
“…The subsequent analysis of these features can provide potential noninvasive biomarkers for clinical-decision support. [19][20][21][22] Radiomics has been used in breast cancer to predict malignancy, 23 pathological complete response to neoadjuvant chemotherapy (NAC), 24 etc. Radiomics combined with clinicopathologic risk factors can increase prediction power 20 and has been applied to predict regional lymph node metastasis in colorectal cancer 25 and bladder cancer.…”
mentioning
confidence: 99%
“…The subsequent analysis of these features can provide potential noninvasive biomarkers for clinical-decision support. [19][20][21][22] Radiomics has been used in breast cancer to predict malignancy, 23 pathological complete response to neoadjuvant chemotherapy (NAC), 24 etc. Radiomics combined with clinicopathologic risk factors can increase prediction power 20 and has been applied to predict regional lymph node metastasis in colorectal cancer 25 and bladder cancer.…”
mentioning
confidence: 99%
“…Compared with traditional methods, the main advantage of deep learning models is its capability in extracting highly representative features in a data‐driven way. Recently, the efficacy of deep neural networks has been evaluated in breast cancer classification tasks . However, these works either used a small‐size dataset or needed manual annotations on lesions during the training phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy of deep neural networks has been evaluated in breast cancer classification tasks. [28][29][30] However, these works either used a small-size dataset or needed manual annotations on lesions during the training phase. Directly localizing breast cancers in 3D radiology images with only image-level supervision has not yet been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…Computer‐assisted diagnosis software was introduced more than a decade ago, but recent developments using neuronal networks and multivariate feature extraction ("radiomics") might have a substantial impact in supporting the image evaluation of radiologists in abbreviated breast imaging protocols: Using such software algorithms, which are known to be able to extract up to 40,000 different image characteristics, might increase diagnostic accuracy, reproducibility, and clinical efficacy of abbreviated protocols. Further, it has been demonstrated that such analyses might even give further insight in histological subtypes and provide prognostic information .…”
Section: Emerging Techniques and Outlookmentioning
confidence: 99%